Southwest Research-Extension Center, Field Day 2002 (Kansas Agricultural Experiment Station Research Reports, 2002)
Report of agricultural research from Southwest Research-Extension Center of Kansas State University.
Keywords: 2002; SRP895; crops; tillage; weed science; insect control; water quality